TolCV1 Has Multifaceted Roles During Vibrio vulnificus Infection - Gong, Yue; Guo, Rui Hong; Rhee, Joon Haeng; Kim, Young Ran (Frontiers in Cellular and Infection Microbiology, 2021)
RtxA1 is a major cytotoxin of Vibrio vulnificus (V. vulnificus) causing fatal septicemia and necrotic wound infections. Our previous work has shown that RpoS regulates the expression and secretion of V. vulnificus RtxA1 toxin. This study was conducted to further investigate the potential mechanisms of RpoS on RtxA1 secretion. First, V. vulnificus TolCV1 and TolCV2 proteins, two Escherichia coli TolC homologs, were measured at various time points by Western blotting. The expression of TolCV1 was increased time-dependently, whereas that of TolCV2 was decreased. Expression of both TolCV1 and TolCV2 was significantly downregulated in an rpoS deletion mutation. Subsequently, we explored the roles of TolCV1 and TolCV2 in V. vulnificus pathogenesis. Western blot analysis showed that RtxA1 toxin was exported by TolCV1, not TolCV2, which was consistent with the cytotoxicity results. Furthermore, the expression of TolCV1 and TolCV2 was increased after treatment of the host signal bile salt and the growth of tolCV1 mutant was totally abolished in the presence of bile salt. A tolCV1 mutation resulted in significant reduction of V. vulnificus induced-virulence in mice. Taken together, TolCV1 plays key roles in RtxA1 secretion, bile salt resistance, and mice lethality of V. vulnificus, suggesting that TolCV1 could be an attractive target for the design of new medicines to treat V. vulnificus infections.